Eye changes related to Zika Vírus infection: an integrative review (Research, Society and Development, 2021)
Recently the Zika virus (ZV) has emerged as an important arbovirus due to its high prevalence. The global expansion of these arboviruses was preceded by the global spread of their vectors. The clinical manifestations of ZV infection include fever, skin rashes and joint pain, as well as ocular manifestations, which are the most recently known manifestations. Objective: to carry out a bibliographic survey and describe the main ocular changes in individuals infected with the Zika virus. Methodology: This is an integrative bibliographic review carried out in the databases PubMed / MEDLINE, SciELO, Science Direct. Results: 16 articles published between 2015 and 2018 were selected. Cataracts, congenital glaucoma, atrophic changes in the optic nerve, loss of the retinal pigment epithelium and presence of a choroid layer, uveitis, hyperpigmentation and collagen of the iris are found in individuals infected with ZV. Conclusion: Eye changes associated with ZV can affect from neonates to adults, and can be a limiting factor in activities of daily living and quality of life. Therefore, it is recommended that further association studies investigate ZK infection and the appearance of eye diseases.